Uncertain times: anthropological approaches to labor in a neoliberal world - Durrenberger, E. Paul, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
The first-ever collection of labor anthropology from around the world, Uncertain Times addresses the theory that traditional labor union organization has been co-opted by the neoliberal policies of corporate capital and become a member service rather than a driver of social movements.--Provided by publisher.
Introduction: Hope for Labor in a Neoliberal World -- 1. Anthropologists, Activists, and the Labor Movement -- Industry. 2. The Gift of Labor: The Town, the Union, and the Corporate State in the Demise of the Swedish Car Industry -- 3. Trade Unions, Labor Conflict, and Contested Institutions in the Swiss Construction Industry -- 4. Union Power and Transnational Corporations in the Argentine Steel Industry -- 5. Agents of Change or Status Quo? Labor NGOs in South China -- 6. Labor Struggles in the Shipbuilding Industry of Piraeus -- 7. The Struggle for Labor Rights in the Maquiladoras of Northern Mexico -- Agriculture. 8. Growers, Unions, and Farm Laborers in Mexico's Baja California -- 9. Policies, Economic Forces, Class Relations, and Unions in Spain's Strawberry Fields -- Retail and Service. 10. Subcontracted Employment and the Labor Movement's Response in Turkey -- 11. Organized Labor in Contemporary Israeli Retail Chains -- 12. National Unions, International Capital, and Bank Workers -- Conclusion: Is There Hope in the Neoliberal World of Labor?
Keywords: Business anthropology; Organizational behavior; Labor unions; Labor unions -- Organizing; Neoliberalism